2011
DOI: 10.1002/jnr.22603
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral reduction of β-amyloid is sufficient to reduce brain β-amyloid: Implications for Alzheimer's disease

Abstract: 2ModGene LLC, Cardiff-by-the-Sea, CaliforniaThree loci that modify b-amyloid (Ab) accumulation and deposition in the brains of a mouse model of Alzheimer's disease have been previously described. One encompasses the Psen2 gene encoding presenilin 2, a component of the g-secretase activity responsible for generating Ab by proteolysis. We show that the activity of mouse Psen2, as measured by levels of mRNA accumulation, unexpectedly is heritable in the liver but not the brain, suggesting liver as the origin of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(79 citation statements)
references
References 29 publications
5
71
1
2
Order By: Relevance
“…Recently it was reported that subchronic administration of imatinib in mice can reduce A␤ levels in plasma and that this decrease in peripheral A␤ was sufficient to reduce A␤ levels in the brain (28). Contrary to these findings, we found subchronic administration of imatinib in rats had no effect on the level of A␤40 in plasma despite achieving a plasma exposure in excess of the cellular IC 50 .…”
Section: Discussioncontrasting
confidence: 99%
“…Recently it was reported that subchronic administration of imatinib in mice can reduce A␤ levels in plasma and that this decrease in peripheral A␤ was sufficient to reduce A␤ levels in the brain (28). Contrary to these findings, we found subchronic administration of imatinib in rats had no effect on the level of A␤40 in plasma despite achieving a plasma exposure in excess of the cellular IC 50 .…”
Section: Discussioncontrasting
confidence: 99%
“…Peptides in general poorly cross the BBB (49,50), but can be transported into the brain if specific transporters and/or receptors with a transport function are expressed in brain endothelium either under physiological (51,52) or pathological conditions, as in the case of RAGE and Aβ transport (43). Recent studies have independently confirmed earlier observations that circulating Aβ is an important precursor for brain Aβ (7,10,33) by demonstrating that peripheral Aβ can accelerate cerebral β-amyloidosis in a mouse model (11) and that liver serves as an important source of brain Aβ (53). These recent findings have extended earlier work showing that circulating Aβ enters the brain via RAGEmediated transport across the BBB, either as a soluble molecule (10) and/or via Aβ-laden monocytes (33), and contributes to the formation of parenchymal amyloid plaques, as shown, for example, in nonhuman primates (54).…”
Section: Discussionmentioning
confidence: 80%
“…Perhaps the most widely studied aspect of BBB with regards to AD, is its role in the clearance and sequestration of amyloid beta to the peripheral circulation (28,(67)(68)(69). Interestingly, individuals with high serum fibrinogen have been shown at greater risk of AD (70,71).…”
Section: Page 17 Of 22mentioning
confidence: 99%